PROBLEMS OF SUBWAY CONSTRUCTION IN COMPLEX ENGINEERING AND GEOLOGICAL CONDITIONS BY THE EXAMPLE OF KHARKІV CITY - Strizhelchik, G. G.; Iegupov, V. Yu. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Scientific, technical and practical problems connected with the construction of subways, such as complex engineering and geological conditions, tunneling need in existing urban development conditions, unfavorable processes emergence during construction and operation are considered. A number of resonant factors that require special decisions when constructing the third subway line ine Kharkiv city have been identified. These factors are large dewatering influence radius threaten surface subsidence and damage of building structures in the area of open tunneling; barrage impact on the groundwater flow in the area of closed tunneling; threat to several buildings located above the tunnels; threat of weak soils dumping in the tunnel face; vibration impact on soils, buildings and structures. Seismic effect assessment on Kharkіv subway objects is discussed.
Keywords: subway; complex conditions; soft soils; accidents